Case Report: Simultaneous Ascending Aortic Dissection and Pulmonary Artery Dissection Combined by Aortopulmonary Fistula After Aortic Valve Replacement - Song, Lihui; Xiong, Sizheng; Li, Jun (Frontiers in Cardiovascular Medicine, 2021)
Aortopulmonary fistula with/without pulmonary artery dissection is an extremely rare and fatal complication of acute aortic dissection and often discovered post-mortem. We present a case with a simultaneous ascending aortic dissection and pulmonary artery dissection combined by aortopulmonary fistula after aortic valve surgery. Unfortunately, the patient died of postoperative complications after surgery. Herein, the anatomical basis for this rare entity and its outcome is explored with emphasis.